Politicians and Economic Policy During the Pandemic: Evidence from Emerging and Developed Countries - Indri Dwi Apriliyanti; Cinintya Audori Fathin (Journal of Central Banking Law and Institutions, 2022)
Our study explores economic policy communication in response to the Covid-19 pandemic crisis. Considering a major role of Twitter in information dissemination, we use tweets as a proxy to examine politicians’ crisis communication strategies in five countries, Australia, Canada, India, Indonesia, and Singapore. By using systematic content analysis approach, the study attested the degree to which SCCT and IRT model can be applied to political realm. We found two strategies, bolstering and mortification, emerge as the most frequently used strategies by politicians. Further, new strategies, i.e information provision and cohesion, as well as new categories, i.e morale boosting, political positioning, and cross border cooperation surfaced which further expanding the SCCT and IRT model in explaining political crisis communication. As this study explores the role of context and situational factors that determine specific strategies, our findings demonstrate no substantial differences among developed and emerging countries. We note the use of combination of bolstering, mortification, and cohesion strategies can be critical for politicians’ career, as they may restore politicians’ reputation, reinforce their political presentation, and foster public trust.